Scheduling of the HVAC system in a real commercial building considering equipment cycling and rebound effects - Faddel, Samy; Sun, Qun Zhou; Tian, Guanyu; Parlato, Alex (Frontiers in Energy Research, 2023)
Commercial buildings consume a large portion of energy and the heating, ventilation, and air conditioning (HVAC) system is the major contributor to this high consumption. Though there are many reported works on the optimal scheduling of HVAC systems, practical considerations such as equipment cycling and possible rebound effects are rarely considered. This paper provides insights into the optimal scheduling of the HVAC system in an actual 3-floor commercial building where the cycling and rebound effects are addressed in the optimization. The experimental results prove that energy cost reduction can be achieved while ensuring temperature comfort and longer life expectancy of the HVAC. The results also show that considering the cycling and rebounds will affect the potential cost reduction.